Operational forecasting inundation extents using REOF analysis (FIER) over lower Mekong and its potential economic impact on agriculture. (April 2023) - Chang, Chi-Hung; Lee, Hyongki; Do, Son K.; Du, Tien L.T.; Markert, Kel; Hossain, Faisal; Ahmad, Shahryar Khalique; Piman, Thanapon; Meechaiya, Chinaporn; Bui, Duong D.; Bolten, John D.; Hwang, Euiho; et al.
Abstract: In the Lower Mekong River Basin floodplains, rice cultivation is highly crucial for regional and global food security. However, prolonged flooding can pose damage to rice cultivation and other socio-economic aspects. Yet, there is no rapid operational inundation forecasting system that can help decision-makers proactively mitigate flood damages. Here, we integrated the so-called Forecasting Inundation Extents using Rotated empirical orthogonal function analysis (FIER) framework with an altimetry-based operational Mekong River level forecasting system and built an operational web application, FIER-Mekong, (https://fier-mekong.streamlit.app/ ) that generates daily skillful forecasted inundation extents (>70% of critical success index) and depths in about 3 and 30 s, respectively, with up to 18-day lead times. One of its applications, predicting flood-induced rice economic losses, is also presented. Had FIER-Mekong being adopted, we estimated that the rice damages, up to 87 and 53 million US dollars during the 2020 and 2021 harvest time, respectively, could have been avoided. Highlights: A new operational inundation forecasting system for Lower Mekong is implemented. It forecasts daily inundation extents in 3 s with up to 18-day lead times. It forecasts daily inundation depths in 30 s with up to 18-day lead times. It allows spatio-temporal rice economic loss prediction on a daily basis. If used, it could have saved 87 and 53 million USD of rice losses in 2020 and 2021.